Relative abundance of stem borer species and natural enemies in rice ecosystem at Madhupur, Tangail, Bangladesh (Journal of the Bangladesh Agricultural University, 2016)
The relative abundance of different stem borer species and their natural enemies with interaction effects were studied at three growth stages of irrigated Boro rice at Madhupur under the district of Tangail, Bangladesh during January to April, 2013. Five stem borer species viz; Yellow stem borer (Scirpophaga incertulas), Pink stem borer (Sesamia inferens), Dark headed stem borer (Chilo polyhcrysus), Stripped stem borer (Chilo suppressalis), White stem borer (Scirpophaga innotata), and nine different natural enemies were collected from the rice fields and recorded. The population of stem borers and natural enemies was highest in tillering stage and lowest in seedling stage. The relative abundance of stem borer species under investigation showed ranking order; yellow stem borer >dark headed stem borer>pink borer>white borer>stripped stem borer and natural enemies as ladybird beetle >long jawed spider>wolf spider>damselfly>carabid beetle>green mirid bug>lynx spider>dragon fly>ear wig. Populations of all five stem borers were positively correlated with ladybird beetle, wolf spider, long jawed spider, lynx spider, damsel fly, dragon fly, green mirid bug and negatively correlated with carabid beetle and earwig.J. Bangladesh Agril. Univ. 12(2): 267-272, December 2014